Teori-teori Kontemporer dalam Penerjemahan - Nur Azaliah Mar; St Kuraedah; Haniah Haniah (Journal of Arabic Education and Linguistic, 2022)
Abstract: Translation as an interesting field of study for language teaching and as a means of communication media, mastery of translation theory as the basis for learning translation also needs to be researched. This study will describe the study of theories used in translation. This research is a literature study that uses descriptive qualitative research methods. The literature study method is used because this research is a theoretical study by collecting data from references and other scientific studies related to translation theories. There are 3 theories in various translation analyzes that are still often used: 1. Translation shift theory from J.C. Catford, 2. The Literal-Idiomatic Theory from Mildred L. Larson, and 3. The Literal-Idiomatic (Freely) Theory from Peter Newmark, of the three theories starting with translating words to free translation. Keywords: Contemporary, Theory, Translation